Modification of Chitosan/PEG4000 dispersed with Lithium Triflate (LiCF\(_3\)SO\(_3\)) as a solid polymer electrolyte for the secondary battery - Sari, Kartika; Haryadi, Arifin Nur Muhammad; Khusaenah, Nur; Sudaryanto; Yulianti, Evi; Utomo, Agung Bambang Setio (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
Secondary battery solid electrolytes attract researchers' attention for being one of the components of the anode and cathode separation in batteries. Currently, battery electrolytes on the market are liquid-based, which have weaknesses in their safety and are not environmentally friendly. Solid-based electrolytes can be a good choice since they excel in the safety and stability of mechanical and electrical properties; however, they still have the disadvantage of low conductivity values ( 10-4 - 10-6 S/cm), thus requiring modification. The solid electrolytes modification using chitosan can be done by adding other polymers and salts as fillers and Li+ ion-making agents. This scientific paper offers an overview of the development of chitosan-based secondary battery solid electrolytes with the addition of PEG4000 polymer and LiCF3SO3. The study was conducted using the solution casting method producing solid electrolytes in the form of membranes. The addition of PEG4000 and LiCF3SO3 affected the microstructure and electrical permittivity of the polymer solid electrolyte membrane. PEG4000 as a plasticizer had no significant effect on inter- and intra-molecular bonds due to poor membrane homogeneity; meanwhile, LiCF3SO3 could increase the permittivity and ionic conductivity of the chitosan polymer solid electrolyte membrane to 3.199 x 10-7 S/cm. The chitosan polymer solid electrolyte membrane with the addition of PEG4000 and 30% LiCF3SO3 salt has an optimal value compared to other salt concentration variations. The results of this research concluded that LiCF3SO3 is evenly dispersed in the chitosan/PEG4000 solid polymer electrolyte membrane enabling it to be used as a secondary battery solid electrolyte.